Corporate Governance Indicators and Firm Value: Evidence of Sharia Compliant Firms from Pakistan - Khalil, Rashid; Bin Shuib , Mohd. Sollehudin; Shahzad , Arfan (International Journal of Psychosocial Rehabilitation, 2020)
This letter intents to test the impact of ownership, business, and board structure on the firm value in case of Shariah compliant firms listed on Pakistan stock exchange. The underpinning objective of current study was whether Shariah compliant firms differ from the non-Shariah compliant firms in case of firm value creation. The findings of current study reveal that ownership structure have significantly linked with firm value (family ownership (+), Concentrated ownership (+), and foreign ownership (-)). The business structure indicates a positive and significant relationship with the firm value. Similarly, in case of board structure the relationship is significant (board independence (-), board size (+), and CEO duality (+)). The findings of current study indicate that Shariah compliant firms significant differ from the non-Shariah compliant firms. Furthermore, the future studies need to consider comparative study for better understanding.